ASPEK PERPAJAKAN TERHADAP PENSION PLAN DAN EMPLOYEE STOCK OWNERSHIP PLAN (ESOP) - Dinda Fali Rifan; Iga Cindy Pratiwi; Siti Kholilah Annisa (UNIVERSITAS MUHAMMADIYAH METRO, 2023)
The purpose of this research is to analyze the implementation of the Employee Stock Ownership Plan (ESOP) in several countries and to analyze the taxation aspects of the Pension Plan and Employee Stock Ownership Plan (ESOP). This research uses a qualitative approach with data collection techniques through literature study. The results of the study show that the Employee Stock Ownership Plan (ESOP) is a form of incentive given by the company to its employees to become owners of company shares by giving employees the opportunity to buy shares at a certain price and time that has been carried out, which aims to provide rewards, create harmony , as well as increasing motivation and commitment to its employees. Ease in the field of taxation is one of the drivers of increased arrests of share ownership by employees. The United States, British Columbia, Canada and Ireland have specific rules governing relief from the issuance of shares to employees. In Indonesia, there is no tax regulation governing the granting of relief for the issuance of shares to employees. Tax regulations in Indonesia stipulate that in the event that the shares are given free of charge, then when the shares are issued they will be subject to Article 21 Income Tax (PPh) on their market value (in the case of being listed on an Exchange) or their nominal value (in the case of not being issued on a stock exchange). However, since 1999, Indonesia has issued regulations governing the tax treatment of stock options, namely by issuing Surat Edaran Direktur Jenderal Pajak Nomor SE-13/PJ.43/1999.